Femtosecond electron pulses production system - S. Rimjaem (2018)
The SURIYA project is designed to generate femtosecond (fs) electron pulses at the Fast Neutron Research Facility (FNRF), Thailand. The fs electron pulses production system consists mainly of a thermionic cathode RF-gun, a magnetic bunch compressor in form of an alpha magnet (α-magnet), a linear accelerator (linac), a beam transport line, and various electron beam diagnostic instruments. This system aims to produce a 20-25 MeV electron beam with micropulses of less than 100 fs in length. Theses pulses can be used either for direct experimentation or to produce fs pulses of intense coherent far infrared radiation (FIR) and/or x-ray. In this paper, an overview of the system and characteristics of its major components will be presented. © 2005 Trans Tech Publications, Switzerland.